1995
DOI: 10.1101/gad.9.19.2421
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions for the poly(A)-binding protein in mRNA decapping and deadenylation in yeast.

Abstract: The first step in the decay of many eukaryotic mRNAs is shortening of the poly(A) tail. In yeast, deadenylation leads to mRNA decapping and subsequent 5' -> 3' exonucleolytic degradation of the transcript body. We have determined that the major poly(A)-binding protein Pablp plays at least two critical roles in this pathway. First, mRNAs in pablA strains were decapped prior to deadenylation. This observation defines a new function for Pablp as an inhibitor of mRNA decapping. Moreover, mutations that inhibit mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
239
1
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(266 citation statements)
references
References 50 publications
(88 reference statements)
22
239
1
3
Order By: Relevance
“…These data suggest that eviction of the last Pab1p molecule triggers turnover. Consistent with this view, decapping becomes independent of poly(A) in mutant strains that lack Pab1p, such that mRNAs with long poly(A) tails are decapped (Caponigro and Parker 1995). The effects of pab1 mutations on cellular mRNA levels may be complex, with contributions from turnover and/ or nuclear processes, such as mRNA 3Ј-end formation (Caponigro and Parker 1995;Amrani et al 1997;Keller and Minvielle-Sebastia 1997;Minvielle-Sebastia et al 1997;J.…”
supporting
confidence: 51%
“…These data suggest that eviction of the last Pab1p molecule triggers turnover. Consistent with this view, decapping becomes independent of poly(A) in mutant strains that lack Pab1p, such that mRNAs with long poly(A) tails are decapped (Caponigro and Parker 1995). The effects of pab1 mutations on cellular mRNA levels may be complex, with contributions from turnover and/ or nuclear processes, such as mRNA 3Ј-end formation (Caponigro and Parker 1995;Amrani et al 1997;Keller and Minvielle-Sebastia 1997;Minvielle-Sebastia et al 1997;J.…”
supporting
confidence: 51%
“…The presence of a poly(A) tail is generally thought to be a critical determinant of mRNA stability+ For some mRNAs, poly(A) shortening or removal is the ratedetermining event in their decay, whereas, for others, it may be an obligate event in their degradation, but it is not the rate-determining step (Chen et al+, 1995;Caponigro & Parker, 1996;+ The presence of a poly(A) tail provides an mRNA with a binding site for poly(A)-binding protein, which, in turn, serves to promote translational initiation and antagonize mRNA decapping in the cytoplasm (Gallie et al+, 1989;Caponigro & Parker, 1995;Tarun & Sachs, 1996)+ In this study, the TRP4-ribozyme allele produces a transcript lacking a poly(A) tail and, as a consequence, it would be predicted that this mRNA would be susceptible to nucleolytic attack and considerably less abundant than its wild-type counterpart+ In contrast, we found that the nonpolyadenylated ribozyme transcript accumulated to levels indicative of little, if any, change in stability+ Maintenance of the stability of the poly(A)-deficient TRP4-ribozyme mRNA is likely to be a result of the action of the ribozyme in generation of the mRNA 39 end, and not to some internal TRP4 sequence features, as deletion of the TRP4 39 UTR resulted in a significant decrease in the amount of TRP4 mRNA+ In support of this idea, a previous study determined that the presence of a ribozyme in an mRNA is not sufficient to render it more labile (Donahue & Fedor, 1997)+ Several plausible explanations could account for the unchanged stability of TRP4-ribozyme mRNA+ The secondary structure formed by the hammerhead ribozyme, or the terminal 29-39cyclic phosphate (Tanner, 1999), instead of a 39-OH, might impede the accessibility of 39 exonucleases to the mRNA+ Alternatively, the absence of a poly(A) tail might uncouple an otherwise linked mechanism in which decapping is triggered by deadenylation (Muhlrad et al+, 1994)+ A more likely explanation is that degradation of the TRP4 mRNA is normally associated with its translation (Jacobson & Peltz, 1996)+ In a manner previously exemplified by the MATa1 mRNA (Parker & Jacobson, 1990), impaired translation of the TRP4-ribozyme mRNA (see below) may reduce the extent to which ribosome-associated factors act to promote decay+…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of mammalian and yeast pre-mRNA 39-end-processing components reveals that, although many homologies can be found, the proteins are not function-ally interchangeable (for a recent review, see )+ An apparent case of divergence during evolution occurs with poly(A)-binding proteins+ Yeast contains a single poly(A)-binding protein (termed Pab1p), which is an essential protein present in both the nucleus and the cytoplasm (Sachs et al+, 1986)+ In the nucleus it stimulates polyadenylation and controls poly(A) tail length (Amrani et al+, 1997;MinvielleSebastia et al+, 1997;Brown & Sachs, 1998), whereas in the cytoplasm it is involved in translation initiation (Sachs & Davis, 1989;Sachs & Deardorff, 1992;Tarun & Sachs, 1995, 1996Le et al+, 1997) and mRNA degradation (Caponigro & Parker, 1995;Boeck et al+, 1998;Coller et al+, 1998)+ In contrast, mammalian cells contain two distinct proteins called poly(A)-binding protein I (PABP1) and poly(A)-binding protein II (PAB II or PABP2)+ PABP1 is predominantly detected in the cytoplasm (Görlach et al+, 1994), whereas PABP2 is localized in the nucleus (Wahle, 1991;Krause et al+, 1994)+ PABP1, which is the mammalian counterpart of yeast Pab1p (51% identity), is apparently involved in both cytoplasmic mRNA stability (Bernstein et al+, 1989;Wormington et al+, 1996;Afonina et al+, 1997;Ford et al+, 1997;Körner & Wahle, 1997) and translation (Craig et al+, 1998), but to date there is no evidence that it participates in nuclear pre-mRNA 39-end processing (see )+ Consistent with its nuclear localization, PABP2 is the mammalian protein involved in polyadenylation+ PABP2 stimulates processive poly(A) addition and controls the size of the tail to be ;250 nt in length (Wahle, 1991(Wahle, , 1995Bienroth et al+, 1993)+ How PABP2 bound to poly(A) tails in the nucleus is replaced by PABP1 in the cytoplasm remains unknown, but recent evidence indicates that both PABP1 and PABP2 shuttle between nucleus and cytoplasm (Afonina et al+, 1998;Chen et al+, 1999)+ Because it is not known when PABP1 exchanges with PABP2, one possibility is that PABP2 crosses the nuclear pores in association with the mRNA and dissoci...…”
Section: Introductionmentioning
confidence: 99%